Stay in Solidarity and Share Equally: An Open Access Journal in Childhood Studies - TORAN, MEHMET; Sackes, Mesut; Göl-Güven, Maden (Istanbul Kultur University, 2020)
Journal of Childhood, Education & Society (JCES) was founded as a product of collective thought under the leadership of Dr. Mehmet Toran in July 2019 by a group of early childhood researchers who conduct both collaborative and independent academic research. Under the light of scientific research, current publishing policies cannot eliminate inequalities in public access for transfer and access of knowledge that is generated for the public weal (Beall, 2013). Particularly, having a limited access to the knowledge in early childhood studies is acknowledged as the first step for constitution of JCES. In this context, we would like to underline that independent researchers who are voluntarily taking part in the emergence of JCES are involved in a very courageous endeavour. This collective constitution takes an important responsibility for the public as well, and we point out that to fulfil this responsibility, it embraces moral and ethical rules as a reference point. Objectives, scope and ethical principles of JCES are determined with the contribution of the editorial board. In addition, we make promise to the larger research community of early childhood area that we will make sure to contribute to the area by giving a priority to high quality of research with robust evidence.
Keywords: Childhood; Education; Society; Open-Access